2004
DOI: 10.1021/je034251+
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Critical Parameters and the Saturation Densities of Dimethyl Ether

Abstract: On the basis of the direct visual observation of the meniscus disappearance and reappearance in an optical cell, 17 saturated liquid densities and 8 saturated vapor densities of dimethyl ether were measured in the temperature range from 301.816 K to the critical temperature, corresponding to a density range from (66.75 to 654.54) kg·m-3. The maximum uncertainties of the saturated liquid and vapor densities are ±0.15 kg·m-3 and ±0.10 kg·m-3, respectively. The uncertainties of temperature were estimated to be wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Comparisons were also made between the TRIDEN correlation and the saturated liquid densities published by different researchers and stored in the Dortmund data bank [17]. The average absolute deviation between the literature values for saturated liquid densities and calculations with the Rackett equation (TRIDEN extrapolation to the saturation pressure) is 0.20% in density for all data available in the range between 273 and 388 K. The densities published by Pall and Maass [18] (between 280 and 388 K, AAD: 0.29%) and Wu et al [12] (302-384 K, 0.16%) as well as data at lower temperatures from Wu et al [19] (between 231 and 368 K, AAD: 0.12%), Maass and Boomer [20] (233 and 262 K, 0.15%), and from Calado et al [21] (at 182 K, 0.84%) are represented well (for all data AAD: 0.18%) by the Rackett equation. This also indicates that the extrapolation behavior is reliable at lower temperatures due to the simplicity of the TRIDEN correlation.…”
Section: Pρt Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons were also made between the TRIDEN correlation and the saturated liquid densities published by different researchers and stored in the Dortmund data bank [17]. The average absolute deviation between the literature values for saturated liquid densities and calculations with the Rackett equation (TRIDEN extrapolation to the saturation pressure) is 0.20% in density for all data available in the range between 273 and 388 K. The densities published by Pall and Maass [18] (between 280 and 388 K, AAD: 0.29%) and Wu et al [12] (302-384 K, 0.16%) as well as data at lower temperatures from Wu et al [19] (between 231 and 368 K, AAD: 0.12%), Maass and Boomer [20] (233 and 262 K, 0.15%), and from Calado et al [21] (at 182 K, 0.84%) are represented well (for all data AAD: 0.18%) by the Rackett equation. This also indicates that the extrapolation behavior is reliable at lower temperatures due to the simplicity of the TRIDEN correlation.…”
Section: Pρt Resultsmentioning
confidence: 99%
“…In addition, the vapor pressure data reported here, and some of the data of Bobbo et al [26][27][28][29][30] and Kennedy et al [43] were used in the fitting process. In the critical region, the saturated liquid and vapor phase densities of Wu et al [12,19] were used to model the critical region. The isobaric heat capacities of Kennedy et al for the saturated liquid phase were used to control the caloric properties at low temperatures.…”
Section: Data Used In the Fitmentioning
confidence: 99%
“…In addition, it can be used for large-scale production of acetic acid, and it has found commercial use as a refrigerant (Ihmels & Lemmon, 2007). Recent investigations of clean alternative fuels have shown that dimethyl ether and its mixtures have excellent properties as diesel fuels and have a promising future as a replacement for fuels obtained from fossil reserves (Wu, Liu, Wang, & Pan, 2004b). It is also used in other ways such as: propellant for aerosol products, (co-)blowing agent for foam, propellant for aerosol products, solvent, extraction agent, chemical reaction medium, fuel for welding, cutting and brazing, multi-purpose fuel (power generation, heating, transportation), and an excellent methylating agent in the dye industry.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary fundamental equation of state was derived by Ref. [2] and our group has also been done some research on vapor pressure, critical properties, saturation densities, surface tension, liquid viscosity and thermal conductivity of dimethyl ether recently [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%